From Monitoring to Mentoring: Transforming Technology Enhanced Academic Supervision for Teachers' Professional Development in Madrasahs - Eci Sriwahyuni; Rifma Rifma; Sulastri Sulastri (Suluah Pasaman, 2026)
Research on academic supervision has been dominated by conventional approaches oriented toward administrative oversight, while studies on the integration of technology into academic supervision as a means of teacher professional development are still limited, particularly in madrasah environments. This study aims to examine the transformation of technology-based academic supervision at MTsN 17 Tanah Datar in supporting teacher professional development. The study used a qualitative approach with a case study design. Participants included the madrasah principal, the deputy principal for curriculum, and teachers selected based on their involvement in implementing academic supervision. Data were collected through in-depth interviews, observation, and document analysis, then analyzed using the interactive model of Miles, Huberman, and Saldaña, with data validity guaranteed through triangulation of sources and methods. The results show that academic supervision develops through five stages, from conventional classroom supervision, evaluation of supervision effectiveness, non-intrusive supervision based on CCTV, reflective supervision based on learning videos, to the use of supervision results as the basis for teacher professional development programs. This transformation encourages a culture of reflection, collaboration, and constructive feedback. This study is limited to a single location, so its generalizability needs to be further tested through quantitative or multi-site research in other madrasah contexts